Effect of heat accumulation on the microstructure of Invar alloy manufactured by multi-layer multi-pass laser melting deposition. (December 2021) - Liu, Ting; Gao, Zhuanni; Ling, Wanli; Wang, Yanni; Wang, Xiaoming; Zhan, Xiaohong
Highlights: A three-dimensional finite element model was established to calculate the temperature field. Multi-layer multi-pass deposited samples of Invar alloy were fabricated by laser melting deposition. The microstructure characteristics differ at different region of the deposited samples. The grain size shows a dimension discrepancy at different region near the fusion line. Abstract: Invar alloy has an important application in the manufacture of composite forming mould. The laser melting deposition (LMD) technology was utilized to fabricate multi-layer multi-pass deposited samples in this study. The effect of heat accumulation on the microstructure of deposition layer (DL) was investigated through experimental and simulation method. A finite element (FE) model was established to study the temperature field distribution in LMD process. Microstructure of DL was investigated by optical microscope (OM), scanning electron microscope (SEM), and energy dispersive spectrometer (EDS). The thermal cycle curves were extracted for analysis. The accumulation of heat during the deposition process would make the higher location DL reach a higher peak temperature. It could be seen from the observation of the transverse section of the deposited samples that the microstructure consisted of elongated cellular crystals and regular cellular crystals. At the bottom of the DL were columnar crystals grown epitaxially along the maximum temperature gradient and gradually transitioned to equiaxed crystals at the top of the DL. EDS detection results showed that there was no element aggregation phenomenon in the DL. The grains in the remelted zone were coarsened due to suffering a state of overheating.